D’une île à l’autre : enjeux de la créolité au féminin - Ana Paula Coutinho (Carnets)
From a reflection on the absence of women – be it as subject, object or point of reference – in most of the founding texts on creolity, we will take a transversal perspective in order to highlight the main issues which, in their turn, establish the expression, through literature, of women migrating between different – material and symbolic – islands. We will resort to examples taken from women writers from the French Antilles – Simone Schwarz Bart, Maryse Condé and Gisèle Pineau –, but also from a woman writer from Cape Verde, Dina Salústio. We will thus aim at evincing the contribution of these voices to the literary assertion of liminality, while trying to avoid a fossilised insular crystallization.